2020
DOI: 10.5194/hess-2020-305
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Random Forest for short-term daily streamflow forecast in rainfall and snowmelt driven watersheds

Abstract: Abstract. In the past decades, data-driven Machine Learning (ML) models have emerged as promising tools for short-term streamflow forecasts. Among other qualities, the popularity of ML for such applications is due to the methods' competitive performance compared with alternative approaches, ease of application, and relative lack of strict distributional assumptions. Despite the encouraging results, most applications of ML for streamflow forecast have been limited to watersheds where rainfall is the major sourc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…e random forest (RF) is one of the most powerful algorithms of ML for data science, which has been widely used in the construction field [14]. e RF model is successfully applied to solve numerous technical issues of civil engineering [15][16][17][18], geotechnical engineering [19][20][21][22], earth sciences [23][24][25], and environmental protection [26,27]. For example, Mohana [17] has used the RF model and 268 experimental data to predict the compressive strength of concrete containing GGBFS.…”
Section: Introductionmentioning
confidence: 99%
“…e random forest (RF) is one of the most powerful algorithms of ML for data science, which has been widely used in the construction field [14]. e RF model is successfully applied to solve numerous technical issues of civil engineering [15][16][17][18], geotechnical engineering [19][20][21][22], earth sciences [23][24][25], and environmental protection [26,27]. For example, Mohana [17] has used the RF model and 268 experimental data to predict the compressive strength of concrete containing GGBFS.…”
Section: Introductionmentioning
confidence: 99%
“…RFs are appealing for a multitude of reasons, including their predictive performance, robustness, speed, nonparametric nature, stability, diagnosis of variable importance, as well as their ability to handle nonlinearity, interactions, noise, and small sample sizes in forcing data (Tyralis et al., 2019). RFs are being used in a variety of applications including water resources and water quality modeling (Suchetana et al., 2017), construction safety risk (Tixier et al., 2016), and used with success in recent years for flow forecasting, primarily at daily and monthly time scales (Abbasi et al., 2021; Al‐Juboori, 2019; Ghorbani et al., 2020; Hussain & Khan, 2020; Li et al., 2019; Liang et al., 2018; Muñoz et al., 2018; Papacharalampous & Tyralis, 2018; Pham et al., 2020).…”
Section: Proposed Methodologymentioning
confidence: 99%
“…In another development, Yao et al [ 59 ], in the field of atmospheric science, used random surface methodology to forecast hail across Shandong Peninsula and reported that random forest model gave excellent results in terms of its ability to forecast hail in the aforementioned studied area. Similarly, Pham et al [ 60 ], in a study, evaluated the efficacy of utilizing random forest to forecast rainfall as well snowmelt which are driven by watersheds which concluded that random forest was superior, in terms of performance, to other machine learning techniques used in the study. In construction and building technology, Han et al [ 61 ] utilized random forest to predict high-performance concrete compressive strength, and the result obtained showed that random forest was highly effective in the prediction of the strength of the aforementioned concrete.…”
Section: Innovation Of the Studymentioning
confidence: 99%